Ketepatan MESS (mangled extremity severity score) pada penentuan amputasi dini fraktur terbuka tibia tipe III sesuai klasifikasi Gustilo - Armis, Armis (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
The amputation and reconstructive procedure of the management of open tibial fracture type III is still of interest and controversy because the amputation effort is considered as a punishment of primary treatment but a reconstructive method in massive lower extremity trauma is difficult. The MESS is a scoring system that can be applied to mangled extremity and help one determines which mangled limb will eventually come to amputation. The record of 28 open tibial fracture type III patients had been reviewed at the SARDJITO hospital 1990-1995. All seven open tibial fracture type Ill C patients with MESS of greater than seven were amputated. According to four tables of blind comparison analyzing MESS value those patients of more than seven was found to have a positive predictive of 100 % that may be best treated by primary amputation. In conclusion the MESS is an early and accurate predictor for identifying the extremity that may be best treated by amputation or reconstruction.Key words : open fracture - MESS - tibial fracture - amputation - mangled extremity